2008
DOI: 10.1097/ico.0b013e318165642c
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric Profile of the Corneal Response to Short-term Reverse-geometry Orthokeratology Lens Wear in Primate Corneas

Abstract: The primate cornea, particularly the corneal epithelium, responds rapidly to the application of reverse-geometry OK lenses with significant epithelial cell shape alterations with short-term OK lens wear. This finding suggests that the corneal epithelium is moldable in response to the physical forces generated by the OK lenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
0
18
0
5
Order By: Relevance
“…It has been postulated that rather than a simple molding or bending effect, there is a central thinning and peripheral thickening accounting for the corresponding topographic change in curvature. 18,19 24 Although there have been sporadic reports of infective keratitis following OK a systematic review of this procedure did not reveal any increased risk directly attributable to overnight OK. 25 No infectious keratitis was seen in this study as well. OK lenses are worn overnight over a short period of 8-9 h unlike the 24 h wearing pattern of extended wear lenses, where the risk is highest.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that rather than a simple molding or bending effect, there is a central thinning and peripheral thickening accounting for the corresponding topographic change in curvature. 18,19 24 Although there have been sporadic reports of infective keratitis following OK a systematic review of this procedure did not reveal any increased risk directly attributable to overnight OK. 25 No infectious keratitis was seen in this study as well. OK lenses are worn overnight over a short period of 8-9 h unlike the 24 h wearing pattern of extended wear lenses, where the risk is highest.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Some studies have also determined OK effects on tear film components, 16 such as inflammatory mediators. 17 These studies conducted both in animals [18][19][20] and humans 6,7,12 have identified corneal changes produced in stromal and epithelial cell density, SBNP thickness and distribution, 7,12 and epithelial layer thickness ans also changes in the levels and distribution of proinflammatory mediators in the tear film samples of OK wearers. 17,21 To date, however, the effects of OK treatment on tear film osmolarity (TFO ) have not yet been examined.…”
mentioning
confidence: 99%
“…В передней строме роговицы в ЦОЗ имело место уве-личение количества активированных кератоцитов до 7,7 ± 2,5 кл./мм² (t = 26,5; p < 0,001) с достоверной раз-ностью между группами пациентов с миопией слабой и средней степени (t = 2,6; p < 0,01). При превышении количества активированных кератоцитов более 2-й сте-пени по классификации (>10 кл./мм²) назначали корне-опротекторную терапию для профилактики осложнений (патент RU на изобретение 2571714 «Способ подбора ортокератологических линз у детей и подростков с мио-пией», 25.11.15) [19].…”
Section: ;15(2s):183-188unclassified
“…В настоящее время у детей и подростков для коррек-ции и контроля миопии применяются различные виды оптических средств коррекции зрения [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], в том чис-ле ортокератологические линзы (ОКЛ) [16][17][18][19][20][21][22][23]. Извест-но, что для создания рефракционного эффекта в дизай-не ОКЛ используется принцип «обратной» геометрии.…”
unclassified
See 1 more Smart Citation